2011
DOI: 10.1091/mbc.e10-07-0567
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial morphology by APC/CCdh1-mediated control of Drp1 stability

Abstract: Mitochondria form an interconnected network that undergoes dynamin-related protein 1 (Drp1)-dependent fission during mitosis. We demonstrate that changes in mitochondrial dynamics as cells exit mitosis are driven through ubiquitylation of Drp1 by the (anaphase- promoting complex/cyclosome and its coactivator Cdh1) APC/CCdh1 complex. Inhibition Drp1 degradation prevents the normal regrowth of mitochondrial networks during G1 phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 54 publications
(78 reference statements)
3
73
0
1
Order By: Relevance
“…However, it is presumable that LIMK2 would regulate DRP1 expression via cell-cycle related events, which is unknown at present. Horn et al 47 reported that DRP1 level drops when cells enter G1 phase, and in turn, DRP1 level gradually increases following release from G1/S arrest. As cyclin D1 is required for G1/S transition and LIMK2 suppresses cyclin D1 expression, 17 overexpression of cyclin D1 followed by LIMK2 could lead neurons to G1/S arrest-like condition that sustains decrease in DRP1 level.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is presumable that LIMK2 would regulate DRP1 expression via cell-cycle related events, which is unknown at present. Horn et al 47 reported that DRP1 level drops when cells enter G1 phase, and in turn, DRP1 level gradually increases following release from G1/S arrest. As cyclin D1 is required for G1/S transition and LIMK2 suppresses cyclin D1 expression, 17 overexpression of cyclin D1 followed by LIMK2 could lead neurons to G1/S arrest-like condition that sustains decrease in DRP1 level.…”
Section: Discussionmentioning
confidence: 99%
“…DRP1 contains several canonical and non-canonical degradation box motifs. Upon release from synchronized cell cycle arrest DRP1 undergoes cell cycle dependent degradation [68]. The ubiquitylation sites of DRP1 have not been identified as of yet and how ubiquitylation of DRP1 is regulated also needs further investigation.…”
Section: Outer Mitochondrial Membrane Fission and Fusionmentioning
confidence: 99%
“…Reduction of the levels or activity of the key mitochondrial fission protein, dynamin-related protein 1 (Drp1, SwissProt O00429 in humans) leads to elevation of CycE levels in various mammalian cells and in Drosophila (Mitra et al, 2012(Mitra et al, , 2009Qian et al, 2012). The emerging model suggests that cell cycle regulators regulate Drp1 (Taguchi et al, 2007;Kashatus et al, 2011;Horn et al, 2011), which, in turn, further regulates CycE levels in proliferating cells (Mitra, 2013). We have previously shown that although loss of Drp1 deregulates CycE in various cell contexts, it promotes aberrant cell proliferation only in the presence of EGFR signaling (Mitra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%